The communication of social and environmental performance to discharge stakeholder accountability : a case study of Talvivaara Mining Company Limited - Rweyendela, Amani (2014)
This thesis presents a case study examining the social and environmental accounting (SEA) decisions and practices of Talvivaara Mining Company limited. Significant local presence and operating in a socially and environmentally sensitive industry has constantly exposed Talvivaara to social and ethical issues. In November, 2012, the company was faced with a major environmental accident when its gypsum pond leaked, releasing toxic substances to the environment, and posing a real threat to the company’s legitimacy. With special reference to this accident and generic social issues, this thesis aimed to ascertain how Talvivaara has utilized the communication of its social and environmental performance to discharge stakeholder accountability. The study used the content analysis method to analyze Talvivaara’s publicly available documents. The first stage was a longitudinal analysis to capture changes in the level of comprehensive reporting on generic corporate social responsibility (CSR) issues, and external verification and feedback solicitation features in the annual reports from 2008 to 2012. The second stage was a cross-sectional analysis of Talvivaara’s 2012 annual report and some selected press and stock exchange releases. This aimed to examine accounts ascribed to the accident and other CSR rhetoric, to establish the legitimation strategies used by Talvivara in the post-accident accounts. The longitudinal analysis revealed an inconsistent reporting pattern across the studied timeline and CSR issues. External verification and report feedback were sought only after the accident. Meanwhile, Talvivaara did not express responsibility for the accident itself but rather implied by the six discerned legitimation strategies used by the company; corrective action, organizational restructuring, normalizing accounts, attention deflection, image enhancement and redefinement of means and ends. Moreover, the accident response actions were exaggerated while the accident’s negative consequences obfuscated. The overall conclusion reached was that instead of discharging the duty of accountability, Talvivaara was more focused on presenting itself in a positive light. This thesis makes some contributions by describing how accountability tools are used to further legitimacy in an unexplored context, and also by showing the complimentary role of longitudinal and cross-sectional analyses.